A real-world study of anlotinib combined with GS regimen as first-line treatment for advanced pancreatic cancer - Zhan, Gouling; Hu, Jianbing; Da, Shijian; Weng, Jie; Zhou, Chuanyi; Wen, Fang; Liu, Songlian; Fang, Fang; Shen, Erdong; Zhou, Qiang; Luo, Pan; Xu, Min; et al. (Frontiers in Endocrinology, 2023)
Background: The timely addition with anlotinib to the GS regime(Gemcitabine, Tegafur-gimeracil-oteracil potassium) may further improve the treatment efficacy for pancreatic cancer(PC), which has not been reported yet. Therefore, our study aimed to evaluate the safety and efficacy of anlotinib combined with GS regimen(hereinafter referred to as GS+A regimen) in the first-line treatment of unresectable or metastatic PC patients. Method: This retrospective real-world study was conducted on patients with unresectable or metastatic PC treated at Yueyang Central Hospital and Yueyang People's Hospital from October 2018 to June 2022. The efficacy was evaluated by overall survival(OS), progression-free survival(PFS), disease control rate(DCR), and objective response rate(ORR), and the safety was assessed by the frequency of critical adverse events(AEs). Results: A total of 71 patients were included in our study, with 41 cases in the GS group and 30 cases in the GS+A group. The mPFS was 12.0 months(95%CI, 6.0–18.0) in the GS+A group, which was longer than 6.0 months(95%CI, 3.0–8.1) in the GS group(P = 0.005). The mOS was 17.0 months(95%CI, 14.0–20.0) in the GS+A group, which was longer than 10.0 months(95% CI, 7.5–12.5) in the GS group(P = 0.018).The GS+A group had higher ORR(50.0% vs 26.8%, P = 0.045) and DCR(83.3% vs 58.5%, P = 0.026). In addition, there was no significant increase in AEs in the GS+A group compared to the GS group, and there were no grade 4-5 AEs and no treatment-related deaths. Conclusion: The GS+A regimen therapy may become a promising treatment for treatment-naive advanced PC, and future prospective studies with larger sample sizes and multiple centers are needed to determine the efficacy and safety of GS+A regimen therapy